Varieties of Belonging Among Migrants: Turkish Migrants in Norway - Meltem Yılmaz Şener (Journal of Economy Culture and Society)
This article examines differentways of belonging among migrants of Turkish origin who were born in Türkiye and are currently living in Norway (in/around Oslo and Drammen). The discussion in the article is based on the findings of semi-structured interviews conducted between March 2019 and August 2020 with 71 Turkish migrants as part of a qualitative study. Different categories of responses to the questions about belonging and the meanings respondents attached to belonging/not belonging are discussed. The paper aims to demonstrate the heterogeneity and complexity of feelings of belonging among the members of an ethnic group that is assumed to feel belonging to their country of origin rather than the destination country in the context of Europe. Additionally, the paper also aims to elaborate on what migrants actually mean when they talk about their belonging (or not belonging) to territories such as the country of origin or destination country, and collectivities like nations. Here it is argued that questioning and criticizing migrants’ feelings of belonging (especially to their countries of origin) as a part of civic integration agendas is an effort to intervene in and have control over their emotions. This claim to the right to intervene in migrants’ emotional lives is approached critically.